Farmer’s Local Wisdom in Agricultural Land Conservation of Dieng Area - Setyowati, Dewi Liesnoor; Benardi, Andi Irwan; Widyastiti, Ririh; Arsal, Thriwaty (Komunitas, 2019)
Dieng area is one of potato producer areas. Land clearing for potato crops has increased land damage. Communities have local wisdom that has not applied by potato farmers. The research aims to find out farmer participation in performing land conservation local wisdom. Purposive sampling is used as a sampling technique with sample indicators consist of people who do farming, knowledgeable people, and young generation. The research location is Sembungan Village that dominates by high slope land and Dieng Kulon Village, which is a flat land. The research samples comprise 60 respondents of 1,428 populations. Data collection technique was done using questionnaire, interview, and observation, whereas data analysis method used percentage frequency. The research result indicates that the forms of farmersâ€™ local wisdom in land conservation include nyabuk gunung, tumpang sari (intercropping), selokan dalam (deep gutter), galengan berbatu/rumput (stony/grassy small dikes), a day-related myth, and manure. Regarding farmer participation in Sambungan Village, 52.31% participate less in conservation according to local wisdom. Based on Conservation Activity Index (Indeks Kegiatan Konservasi/IKK), 47.69% farmers did not participate in land conservation. According to the index, only 23.59% farmers in Dieng Kulon Village perform land conservation.Â